TINGKAT PERTUMBUHAN DAN KEBUTUHAN UNSUR HARA PADA TEGAKAN HTI Gmelina arborea Roxb (The Plant Growth Rates and Nutrient Requirements of Gmelina arborea Roxb. Plantation Forest) - , Cahyono Agus ([Yogyakarta] : Fak. Kehutanan UGM, 2000)
Forest sustainable management needs infonnation on plant growth and nutrient requirement monitoring. Aboveground biomass and nutrient stock of Gmelina arborea Roxb plantation forest were investigated by allometric model, by felling 24 tICesat several diameter classes and were cutted at every 1 meter tree height for dried weight and nutrient analysis. Plant parts were sorted to stem, big branch (&gt